2018
DOI: 10.1038/s41467-018-07608-w
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 mediates cellular distribution of HER2 and affects trastuzumab binding and therapeutic efficacy

Abstract: Human epidermal growth factor receptor 2 (HER2) gene amplification and/or protein overexpression in tumors is a prerequisite for initiation of trastuzumab therapy. Although HER2 is a cell membrane receptor, differential rates of endocytosis and recycling engender a dynamic surface pool of HER2. Since trastuzumab must bind to the extracellular domain of HER2, a depressed HER2 surface pool hinders binding. Using in vivo biological models and cultures of fresh human tumors, we find that the caveolin-1 (CAV1) prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
174
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(186 citation statements)
references
References 63 publications
11
174
0
1
Order By: Relevance
“…Temporal modulation of CAV1 with the cholesterol-lowering drug lovastatin increases HER2 availability at the cell membrane to enhance the binding of trastuzumab to gastric cancer cells (27). Our previous work showed an increase in HER2 half-life at the cell membrane of NCI-N87 gastric cancer cells.…”
Section: Lovastatin Increases Her2 Dimerization Without Altering Her2mentioning
confidence: 87%
See 2 more Smart Citations
“…Temporal modulation of CAV1 with the cholesterol-lowering drug lovastatin increases HER2 availability at the cell membrane to enhance the binding of trastuzumab to gastric cancer cells (27). Our previous work showed an increase in HER2 half-life at the cell membrane of NCI-N87 gastric cancer cells.…”
Section: Lovastatin Increases Her2 Dimerization Without Altering Her2mentioning
confidence: 87%
“…However, clinical studies have reported that 89 Zrlabeled antibodies do not always accumulate in HER2-positive tumors (25). Immunohistochemical staining of gastric tumors reveals nonuniform membrane expression of HER2 (15), which contributes to low accumulation of antibodies in these tumors (18,26,27). Moreover, endocytic trafficking mediates HER2 internalization and further reduces the availability of HER2 at the cell membrane, preventing binding with antibodies such as trastuzumab and pertuzumab and dampening their therapeutic efficacy (27)(28)(29)(30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous studies have demonstrated that HER2 is localized to cholesterolrich membrane raft regions where it may colocalize with GM1 (50) as well as CAV1 (51). Recent studies by Pereira and colleagues (52) suggested an inverse relationship between HER2 and CAV1 protein expression in a large collection of cancer cell lines and in examples of human gastric tumor specimens. In the present study, we were, however, unable to find a significant association between CAV1 expression and HER2 status in vitro as well as in a large, populationbased breast cancer cohort.…”
Section: Discussionmentioning
confidence: 98%
“…According to this scenario, the most obvious strategy would be to alleviate the hypoxic situation by, for example, tumor vessel normalization or actions that normalize CAV1 localization to allow more efficient targeting also of hypoxic tumor regions and potentially other niches distinguished by CAV1 clustering at the cell periphery. Interestingly, in models of gastric, bladder, and breast cancer, increased HER2 cell surface availability and improved trastuzumab therapy by disrupting CAV1-mediated HER2 internalization using the cholesterol lowering drug lovastatin were demonstrated (52). In the case of T-DM1, however, one would like to achieve the opposite effect, i.e., increased membrane cholesterol loading and CAV1-mediated HER2 internalization.…”
Section: Discussionmentioning
confidence: 99%